NAF, OAF, or Noncooperation: Which Protocol to Choose?. (13th December 2007) - Saadani Saadani, Ahmed Ahmed; Traoré Traoré, Olivier Olivier
Abstract : The two main Amplify and Forward cooperative protocols are the orthogonal (OAF) and the nonorthogonal one (NAF). In this paper, we consider a given source, N relays, a destination, and a channel realization and we try to resolve the following problem: what is the best way to communicate: without cooperation or using one of the two cooperative protocols? This is equivalent to a power-sharing problem on the cooperation frame between source and relays aiming to the short-term channel capacity maximization. The obtained solution shows that cooperative protocol choice depends only on the available power at the relays. However the decision to cooperate depends on the channel conditions. We show that our power allocation scheme with relay selection improves the outage probability compared to the selective OAF and the NAF protocols and has a significant capacity gain.